Cyclic carbopalladation of alkynes terminated by carbonylative amidation - Copéret, Christophe; Ma, Shengming; Sugihara, Takumichi; Negishi, Ei-ichi (Tetrahedron, 1996)
Termination of cyclic carbopalladation of alkynes via carbonylative lactamization can be achieved more satisfactorily with alkenyl or aryl halides containing an ω-sulfonamido group than with those containing an ω-amino group. The method appears to be generally satisfactory for the preparation of fused cyclic systems consisting of six-membered rings, while the other cases require further development. Intramolecular lactamization of acylpalladium derivatives with internal carboxamides and sulfonamides and its application to the development of cyclic carbopalladation-carbonylative lactamization cascades